(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
The initial processing of raw cotton includes cleaning it from impurities, which is considered one of the main technological stages, significantly influencing fiber separation and subsequent cleaning operations.